Do IMF Programs Stimulate Private Sector Investment? - Bomprezzi, Pietro (IMF Working Papers; Working Paper, 2022)
This paper provides new evidence on the role of IMF programs in stimulating private sector investments. Using detailed firm-level data on tangible fixed assets and a local projection methodology, we first estimate the dynamic response of firm investments to the approval of an IMF arrangement. We find that distinguishing between GRA and PRGT financing matters for the path of firm investment and its growth, and we also document the presence of two financial channels; the degree of firms' external financial dependence and firms' sectoral uncertainty. Exploiting these firm-level characteristics, we employ a difference-in-differences approach to understand the mechanisms through which the approval of an IMF arrangement propagates in the private sector. We find that the more firms rely on external finance and the more they are subject to uncertainty, the less binding these financial frictions become, and hence the more firms invest following a program approval. Finally, using ownership data, we find that private investments are stimulated more for domestic firms. The presence of a private investment transmission channel could help improve our understanding of what factors could affect the success and effectiveness of IMF programs.